Analysing yield trends in the South African sugar industry. (December 2015) - Jones, M.R.; Singels, A.
Abstract: A perception exists in the South African (SA) sugar industry that sugarcane yields are declining. The objective of this study was to quantify yield decline in the SA sugar industry to inform future research and extension efforts to decrease yield gaps. Regional trends in cane yield were calculated from mill-level cane delivery and harvest area data. Benchmark simulated yields for each region were estimated by the Canesim Crop Forecasting System, using inferred harvest age and observed weather data. Actual yields were annualised to remove harvest age effects and then expressed as fractions of corresponding simulated yields, in order to remove effects of inter-seasonal variations in weather. Trends in this yield ratio (YR) were calculated for several regions and grower categories. Yield decline was defined as a decreasing trend in YR over time (1981–2010). Applying this methodology to historic production data for the South African sugar industry revealed that large scale grower (LSG) yield ratios have declined significantly over the period 1986 to 2010, for the South Coast (1.12%/year) and North Coast (1.24%/year). LSG yield ratios increased in Zululand and the Northern irrigated regions, suggesting that growers were able to cope with deteriorating weather and/or exploit technology improvements. Small-scale grower (SSG) yield ratios declined from 1993 to 2010 by 1.73%/year in the Northern Irrigated region. Since 2001 industry average LSG yield ratios declined by 1.97%/year compared to a decline of 2.37%/year for SSG yields (both significant). On a regional basis SSG yield ratios declined in the Midlands (1.43%/year) and Zululand (3.33%/year) regions. Yield decline was perceived by stakeholders to be caused mainly by soil degradation, decreased investment as a result of unresolved land claims, and increasing pest and weed pressures, and suggested increased top/sub-soil liming, green manuring, in-field traffic control and soil and leaf testing as possible means of addressing yield decline. Closing the gap between current and maximum economically-attainable yields has the potential to increase annual industry production by approximately 32% (6.3 million t), and annual grower revenue by ZAR 2.6 billion (based on 2006–2010 industry production). It is recommended that research and extension efforts should be focussed on further understanding and addressing yield decline, particularly for LSGs and SSGs in the Midlands region, LSGs in coastal regions, and SSGs in the Northern Irrigated and Zululand regions. Highlights: Yield trends for five regions were quantified using actual and simulated yield data. Significant yield decline (≈ 2%/year) was observed nationally from 2001 to 2010. Soil degradation was perceived to be a major cause of yield decline. The exploitable yield gap is worth 6.3 million t cane/an (ZAR 2.6 billion/an).